2019
DOI: 10.1088/1361-6463/ab30ed
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response of photorefraction in vanadium and magnesium co-doped lithium niobate

Abstract: Vanadium and magnesium co-doped LiNbO 3 (LN) crystals were grown, and their photorefractive properties were studied in the visible spectral region. At 488 nm the shortest response time of 80 ms was achieved for an LN crystal co-doped with 0.1 mol% V 2 O 5 and 6.0 mol% MgO, which is the more rapid than other reported doped LN crystals in the same wavelength region. The sensitivity of this crystal reaches 17 cm J −1 with an adequate diffraction efficiency of 4.0%. A schematic diagram for energy level is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…To realize a nonvolatile readout, several methods have been developed so far, i.e., thermal fixing, electrical fixing, and two-step recording [14,22]. Though, up to now, there is good improvement in the response speed of the various doped LN crystals [23,24,25,26], much research is needed to get a practical fast responsive material with a high diffraction efficiency. Recently it was found that vanadium doping in LN elicited shortening of the response time [18,19,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…To realize a nonvolatile readout, several methods have been developed so far, i.e., thermal fixing, electrical fixing, and two-step recording [14,22]. Though, up to now, there is good improvement in the response speed of the various doped LN crystals [23,24,25,26], much research is needed to get a practical fast responsive material with a high diffraction efficiency. Recently it was found that vanadium doping in LN elicited shortening of the response time [18,19,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent dopants: both V 3+ and Mo 3+ ions are predicted to self-compensate. Experimental data from [18] support V 3+ doping at the lithium site, as with V 2+ .…”
Section: Hexavalent Dopantsmentioning
confidence: 74%
“…Divalent dopants: the calculations predict that, for V 2+ , self-compensation (simultaneous doping at lithium and niobium sites) and doping at the lithium site with lithium vacancy compensation are most likely. It is noted that V 2+ Li defects have been observed experimentally [18]. Trivalent dopants: both V 3+ and Mo 3+ ions are predicted to self-compensate.…”
Section: Hexavalent Dopantsmentioning
confidence: 94%
See 2 more Smart Citations